Does tooth brushing prevent dental caries among children? A systematic review and meta-analysis - Supinder Sudan; T L Ravishankar; Amit Tirth; M D Nazamuddin Tafadar (Wolters Kluwer Medknow Publications, 2023)
Introduction: Dental caries is the most widespread noncommunicable disease, which needs immediate attention. Globally, it has been estimated that around 60%-90% of school children are affected with dental caries. These carious teeth can be prevented by simple, cost-effective interventions at the individual and community levels. Various studies reported the role of oral hygiene practices particularly the frequency of brushing of teeth in improving oral health status with varying success. Hence, this meta-analysis was undertaken to determine the effect of oral hygiene practices particularly the frequency of brushing in preventing dental caries in children. Methods: The PubMed, Cochrane, Google Scholar, and Scopus databases were searched from January 1, 2000 to October 31, 2022. Hand-searching was performed for relevant journals. Reference articles including children from 3 to 5 years old were retrieved and exported to Mendeley Desktop 1.13.3 software. The risk of bias was assessed using the Newcastle-Ottawa scale for cross-sectional studies. Articles were further analyzed using Open Meta-Analyst. Results: The studies included in qualitative synthesis were 27 and 7 were included in meta-analysis. The pooled prevalence of dental caries among children who brushed once a day and twice a day was 48.7% and 36.6%, respectively. The odds of having dental caries in children who brushed their teeth oncea day was found 1.58 times higher than in those who brushed their teeth twice a day. The absolute reduction in dental caries was 11.3% among those who brushed their teeth twice a day than those who did it once a day (95% confidence interval: 3.2%-19.5%, I2 = 79.59%, P < 0.001). Conclusion: Brushing twice a day after 3 years of birth can lead to the prevention of dental caries at the individual and community level. Hence, tooth brushing twice a day can act as major preventive program and one should teach the children when they are young and provided supervised tooth brushing to prevent dental caries.